KESESUAIAN LAHAN BEBERAPA JENIS TANAMAN KEHUTANAN UNTUK PENGEMBANGAN HUTAN RAKYAT DI SUB DAS TEMON KABUPATEN WONOGIRI - , AHMAD SOLIKIN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Human needs and the competition on the ever increasing use of land, require the management of a serious effort to avoid potential conflicts of land resources. The existence of bare lands should be used for the development of community forests in order to improve forest surrounding communitiesâ welfare. Land suitability as a depiction of the suitability level for a particular use, is needed in the development of community forests. Research was conducted in Tem Sub-watershed, Batuwarno sub-district located in an bare land. This research aims to analyze land suitability for various forestry plant species based on Temon sub-watershed land characteristic and quality for the development of community forest in Temon sub-watershed. Land suitability was conducted with matching method or comparison, which is comparing choosen plant growth requirements with land characteristics and qualities. Plants that are considered are teak (Tectona grandis), acacia (Acacia auriculiformis), mahagony (Switenia mahagoni), Albizia (Albizia falcataria), dan cajeput tree (Melaleuca leucadendron). Research was conducted by dividing research location into nine land unit by overlaying soil type map, slope map, land use map and rainfall map. The result of this research shows that actual condition of considered plant has a permanent not suitable (N2) land suitability class for all land units. Salinity became a limiting factor for all plant species. Followed by the erosion rate becomes a limiting factor for all types of crops throughout the land unit except for land unit ALim 1. The depth of the root as a limiting factor of all plants in soil litosol land unit types. Water availability became a limiting factor for albizia and mahagony in all land units. Keywords : land suitability, community forest, matching